Report of the Steering Committee on Social Welfare for the Tenth five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Report of the Steering Committee on Social Welfare for the Tenth Five-Year Plan (2002–2007), constituted by the Planning Commission under the chairmanship of Dr. D.N. Tiwari, provides a comprehensive review of social welfare policies, institutional mechanisms, and legislative frameworks in response to the rapidly changing socio-economic environment shaped by liberalization and planned development. Recognizing that economic growth alone cannot address deep-rooted social vulnerabilities, the report emphasizes the need for an integrated, preventive, and developmental approach to welfare, particularly for marginalized groups including persons with disabilities, social deviants such as juvenile delinquents and substance abusers, and other disadvantaged populations such as the elderly, destitute women, street children, and the infirm. It highlights the erosion of traditional family and community support systems, rising urban migration, displacement due to development projects, and the growth of social pathologies as critical challenges requiring coordinated intervention. The Committee calls for strengthening constitutional and legislative safeguards, enhancing professional capacity within welfare institutions, improving standards in residential care facilities, promoting non-institutional and community-based rehabilitation, and ensuring balanced expansion of services in rural and underserved regions. It further underscores the importance of greater involvement of NGOs, corporate and voluntary sectors, and effective devolution of powers to Panchayati Raj Institutions under the 73rd and 74th Constitutional Amendments to ensure participatory planning and delivery. By proposing targeted strategies, institutional reforms, improved monitoring mechanisms, and defined financial allocations, the report envisions a responsive and professionally managed social welfare framework capable of empowering the disabled, reforming social deviants, and caring for the most vulnerable sections of society during the Tenth Plan period.
Government of India Planning Commission New Delhi November-2001
Keywords: Social Welfare Sector; Tenth Five-Year Plan; Vulnerable Groups; Persons With Disabilities; Social Deviants; Disadvantaged Sections; Institutional Reform; Panchayati Raj Institutions; Non-Governmental Organizations; Rehabilitation Programmes; Preventive And Developmental Approach; Financial Requirements